A comparison of the ballistic behaviour of conventionally sintered and additively manufactured alumina - Appleby-Thomas, Gareth J.; Jaansalu, Kevin; Hameed, Amer; Painter, Jonathan; Shackel, James (Elsevier, 2019)
Production of ceramic armour solutions on-demand/in-theatre would have significant logistical and military advantages. However, even assuming that such technologies could be successfully deployed in the field, such near net-shape manufacturing technology is relatively immature compared to conventional sintering of ceramics. In this study, the ballistic performance of a series of additively manufactured (AM)/rapidly-prototyped (RP) alumina tiles of 97.2% of the density of Sintox FA™ were investigated using both forward- and reverse-ballistic experiments. These experiments, undertaken with compressed gas-guns, employed the depth-of-penetration technique and flash X-ray as primary diagnostics to interrogate both efficiency of penetration and projectile-target interaction, respectively. The RP alumina was found to exhibit useful ballistic properties, successfully defeating steel-cored (AP) 7.62 × 39 mm BXN rounds at velocities of up-to c.a. 850 m/s, while exhibiting comparable failure modes to conventionally sintered armour-grade Sintox FA™. However, where a <1% by vol. Cu dopant was introduced into the RP material failure modes changed dramatically with performance dropping below that of conventionally sintered alumina. Overall, the results from both sets of experiments were complimentary and clearly indicated the potential of such RP materials to play an active role in provision of real-world body armour solutions provided quality control of the RP material can be maintained.
Keywords: Additive manufacture; Rapidly prototyped; Body armour; Ballistics; Ceramics